READING CULTURE AS A FACTOR IN SHAPING THE SOCIAL IDENTITY OF YOUNG CREATORS (Eureka Journal of Humanities and Social Research, 2026)
This article examines the significance of reading culture, particularly the reading of fiction, in shaping the social identity of young creators, specifically young poets and writers, based on theoretical and empirical research. Special attention is also paid to the analysis of the social identity and its stable elements, such as leisure activities, social functions, and social activity. In addition, within the framework of the article, an empirical study was conducted using the expert survey method, and conclusions and recommendations were formulated based on the obtained results. Furthermore, the indicators influencing the impact of reading on the social identity of young creators were identified.
Keywords: Social profile, book reading, social function, social status, leisure time, book, fiction literature.